2013
DOI: 10.1088/2041-8205/770/1/l12
|View full text |Cite
|
Sign up to set email alerts
|

THE DETECTION OF THE LARGE-SCALE ALIGNMENT OF MASSIVE GALAXIES AT z ∼ 0.6

Abstract: We report on the detection of the alignment between galaxies and large-scale structure at z ∼ 0.6 based on the CMASS galaxy sample from the Baryon Oscillation Spectroscopy Survey Data Release 9. We use two statistics to quantify the alignment signal: (1) the alignment two-point correlation function that probes the dependence of galaxy clustering at a given separation in redshift space on the projected angle (θ p ) between the orientation of galaxies and the line connecting to other galaxies, and (2) the cos(2θ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
58
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 48 publications
10
58
0
1
Order By: Relevance
“…Lee & Erdogdu 2007;Faltenbacher et al 2009;Li et al 2013;Tempel & Libeskind 2013;Zhang et al 2013;Pahwa et al 2016). There is also agreement with Wang et al (2009) for main galaxies of groups.…”
Section: Early-type Galaxiessupporting
confidence: 65%
See 1 more Smart Citation
“…Lee & Erdogdu 2007;Faltenbacher et al 2009;Li et al 2013;Tempel & Libeskind 2013;Zhang et al 2013;Pahwa et al 2016). There is also agreement with Wang et al (2009) for main galaxies of groups.…”
Section: Early-type Galaxiessupporting
confidence: 65%
“…For a straight isolated filament, DALE is equivalent to the direction of the spine. In principle, our approach is similar to the alignment correlation function method developed by Faltenbacher et al (2009) and Li et al (2013).…”
Section: Introductionmentioning
confidence: 99%
“…Mandelbaum et al 2006;Okumura et al 2009;Hirata et al ⋆ vuitert@ucl.ac.uk 2007; Joachimi et al 2011;Li et al 2013;Singh et al 2015), in N -body simulations (e.g. Croft & Metzler 2000;Hopkins et al 2005) and in hydrodynamical simulations (Codis et al 2015;Velliscig et al 2015;Chisari et al 2015Chisari et al , 2016Tenneti et al 2016;Hilbert et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the major axes of LRGs at z∼ 0.3 are correlated up to 30 ∼70Mpc/h (Okumura et al 2009;Li et al 2013), as shown by the points in upper left panel of Fig.3. Okumura et al also found that if the major axis of LRG follows that of the dark matter perfectly, the predicted alignment from N-body simulation is higher than the data (red dashed line), but if there is an average misalignment about 35…”
Section: Resultsmentioning
confidence: 71%
“…(e.g., Yang et al 2006). On large scales, it is found that the shape of Luminous Red Galaxies (LRGs) are correlated up to scales of 30∼70Mpc/h (Okumura et al 2009;Li et al 2013).…”
Section: Introductionmentioning
confidence: 99%